AB0383 CARDIAC INVOLVEMENT IN RHEUMATOID ARTHRITIS: A COMPARATIVE TRANSTHORACIC ECHOCARDIOGRAPHY STUDY - Sarraj, R.; Brahem, M.; Ibn Hadj Amor, H.; Jomaa, O.; Ben Salem, A.; Jebali, B.; Kraiem, S.; Rouabhia, R.; Hachfi, H.; Mohamed, Y. (Annals of the rheumatic diseases, 2023)
BackgroundCardiac involvement in rheumatoid arthritis (RA) is one of the most frequent and severe extra-articular manifestations, but it is often under-diagnosed.ObjectivesIn this context, we conducted this study, whose objective is to determine the prevalence and types of cardiac abnormalities in patients with RA using the transthoracic echocardiography (TTE) and to compare them with control subjects.MethodsWe performed a comparative cross-sectional study conducted in Taher Sfar Hospital, Mahdia, Tunisia. Each patient underwent a TTE coupled with Strain technique.ResultsSeventy-two patients with RA according to the ACR/EULAR 2010 criteria and 72 control subjects (control group) were included. In our study, there was a clear female predominance in both groups with a sex ratio of 0.07 in the RA group and a sex ratio of 0.05 in the control group (p=1). The mean age of RA patients was 52.9 ± 11.72 years [21-75 years] and that of the control group was 49.26 ± 10.74 years [19-76 years] (p=0,06). Abnormalities detected by TTE were more frequent in subjects with RA compared with the control group (80.6% vs 36.1%; p < 0.01) and they were asymptomatic in 65.5% of cases of RA group. Pericardial effusion was more frequent in the RA group compared with the control group but without significant difference. Valvular involvement was significantly more frequent in patients with RA compared to the control group (45.8% vs 1.4%; p<0.01) with predominance of tricuspid involvement (31.9%). Left ventricular diastolic dysfunction was more frequent in RA patients compared with the control group with a significant difference (36.1% vs 13.9%; p<0.01). Regarding the left ventricular systolic dysfunction, left ventricular ejection fraction impairment was absent in both groups, but subclinical left ventricular myocardial damage assessed by the Global Longitudinal Strain (GLS) method was detected in 37.5% of RA patients and 16.6% of control subjects (p<0.01). The mean of GLS in RA patients was -17.8% ± 2.9 [-22 to -10.7%], while it was -19.4% ± 1.9 [-24.7 to -15.7%] in control subjects. Left ventricular hypertrophy was detected on TTE in 22.2% of RA patients and in 6.9% of control group (p<0.01). Pulmonary arterial hypertension was present only in the RA group (2.8% of cases).ConclusionOur study showed that cardiac involvement is more frequent in RA than the general population, hence the interest of systematic screening, in order to improve the quality of life and the vital prognosis of patients.References[1]Shenavar Masooleh I, Zayeni H, Haji-Abbasi A, Azarpira M, Hadian A, Hassankhani A, et al. Cardiac involvement in rheumatoid arthritis: A cross-sectional study in Iran. Indian Heart J 2016;68:332–5.[2]Guedes C, Bianchi-Fior P, Cormier B, Barthelemy B, Rat AC, Boissier MC. Cardiac manifestations of rheumatoid arthritis: A case-control transesophageal echocardiography study in 30 patients. Arthritis Care Res 2001;45:129–35.Acknowledgements:NIL.Disclosure of InterestsNone Declared.